2003
DOI: 10.1038/sj.ijir.3900946
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for the vascular components of erectile dysfunction in patients on renal replacement therapy

Abstract: A total of 76 male patients on renal replacement therapy (RRT) were investigated. Erectile dysfunction (ED) was defined as insufficient erection during visual erotic stimulation (VES) or during sleep as measured with Rigiscan s and Erectiometer s . Data on medical history, physical examination, and laboratory variables were collected. Furthermore, penile pharmacological duplex ultrasonography (PPDU) was performed. Univariate and multivariate logistic regressions were used to determine prognostic values and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thus, according to many writers, these pathologies are involved in the development of ED ( 7 , 20 , 25 ). Chronic liver disease related to hepatitis virus B or C and heart failure, which are described as potentiating factors of sexual dysfunction in patients on dialysis ( 9 , 19 , 20 ), were objectified in one-third of our patients with 95.5% of them presenting ED. Several widely prescribed therapeutic classes, including β -blockers and diuretics, have been implicated in the onset of ED in patients on dialysis ( 16 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, according to many writers, these pathologies are involved in the development of ED ( 7 , 20 , 25 ). Chronic liver disease related to hepatitis virus B or C and heart failure, which are described as potentiating factors of sexual dysfunction in patients on dialysis ( 9 , 19 , 20 ), were objectified in one-third of our patients with 95.5% of them presenting ED. Several widely prescribed therapeutic classes, including β -blockers and diuretics, have been implicated in the onset of ED in patients on dialysis ( 16 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 91%
“…These results are similar to previous data reported by Seck et al and Nassir et al who found respectively prevalence of 81.4% in Senegal ( 5 ) and 83% in Saudi Arabia ( 6 ). Lower prevalence of ED has been reported in patients on dialysis living in Spain ( 7 ), Brazil ( 8 ), and Netherlands ( 9 ) (respectively 60%, 54.9%, and 69%). CIGOP in 1981 showed that more than 50% of male patients with CKD showed erectile dysfunction ( 10 ) The mild and moderate grades of ED, with a prevalence of respectively 28.8% and 27.4%, were the most represented severities in our patients.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, according to many writers, these pathologies are involved in the development of ED (7,20,25). Chronic liver disease related to hepatitis virus B or C and heart failure, which are described as potentiating factors of sexual dysfunction in patients on dialysis (9,19,20), were objectified in one-third of our patients with 95.5% of them presenting ED. Several widely prescribed therapeutic classes, including β -blockers and diuretics, have been implicated in the onset of ED in patients on dialysis (16,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ED, four grades of severity were defined as follows: mild (score, 17-21); light (score, 12-16); moderate (score, [8][9][10][11]; and severe (score, 5-7)…”
Section: Methodsmentioning
confidence: 99%